2004
DOI: 10.1096/fj.03-1378fje
|View full text |Cite
|
Sign up to set email alerts
|

Gene structure and organization of the human β‐secretase ( BACE ) promoter

Abstract: The first step in the generation of the amyloid-beta peptide (Abeta) deposited in the brains of patients with Alzheimer's disease (AD) is the processing of the larger Abeta precursor protein (APP) by an integral membrane aspartyl protease named the beta-site APP-cleaving enzyme (BACE). We present the genomic organization of the BACE gene. BACE mRNAs are synthesized as nine exons and eight introns from a 30.6 kb region of chromosome 11q23.2-11q23.3. Regulation of BACE may play an important role in regulating th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
155
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 166 publications
(160 citation statements)
references
References 41 publications
4
155
0
Order By: Relevance
“…Other studies regarding BACE1 gene promoter reported that a 4.1 kb region contained BACE1 promoter. A 2.4 kb fragment of the human BACE 5 0 -flanking region, which was similar to our uBACE-2K, was found to bind to Sp1 and AP2 transcription factors Sambamurti et al, 2004). However, those studies did not examine the mechanism underlying the activation of BACE1 promoter.…”
Section: Discussionmentioning
confidence: 64%
“…Other studies regarding BACE1 gene promoter reported that a 4.1 kb region contained BACE1 promoter. A 2.4 kb fragment of the human BACE 5 0 -flanking region, which was similar to our uBACE-2K, was found to bind to Sp1 and AP2 transcription factors Sambamurti et al, 2004). However, those studies did not examine the mechanism underlying the activation of BACE1 promoter.…”
Section: Discussionmentioning
confidence: 64%
“…This does not exclude SP1 from an active role in latent Pbinduced pathogenesis. Although the APP and BACE1 promoters from humans and primates contain sites for SP1 binding (Song and Lahiri, 1998;Sambamurti et al, 2004), the specific position of these sites differ with regard to their respective transcription start sites. For example, active SP1 sites in the APP gene appear in its 5Ј-untranslated region (UTR) (Villa et al, 2004), whereas the active SP1 site in the BACE1 promoter is ϳ1 kb upstream of the transcription start (Christensen et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…The upstream sequences of the BACE1 gene promoter are highly conserved among rat, mouse, and human, indicating that this region contains regulatory elements that modulate BACE1 gene transcription (11)(12)(13). We identified a putative PPAR␥ consensus sequence in the region located between nucleotides Ϫ1356 and Ϫ1338.…”
Section: Discussionmentioning
confidence: 99%
“…The untranslated 5Ј-BACE1 transcript leader contains upstream ORFs that can reduce the translation of the main ORF (10). The BACE1 gene promoter region was recently cloned, and several putative transcription factor-binding sites were identified (11)(12)(13).…”
mentioning
confidence: 99%